2020
DOI: 10.1364/ol.384771
|View full text |Cite
|
Sign up to set email alerts
|

Mode insensitive switch for on-chip interconnect mode division multiplexing systems

Abstract: A mode insensitive switch is proposed and experimentally demonstrated on a silicon-on-insulator platform using a balanced Mach–Zehnder interferometer structure with a mode insensitive phase shifter for on-chip mode division multiplexing interconnects. Switching the first three quasi-transverse electric (TE) modes, consuming less than 40 mW power is demonstrated. The whole system exhibits approximately − 2 , − 3.7 , and − 5.2 d B in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…1(c). All the parameters are optimized according to our previous work reported in [10]. The MZI consists of two 2 × 2 multimode interferometers (MMIs) connected by 4 µm wide Si waveguides with 100 µm long S-bend to prevent the thermal crosstalk induced by 200 µm long and 6 µm wide Titanium-tungsten (TiW) phase shifter placed between the two MMIs and 2 µm above one of the MZI balanced paths (Fig.…”
Section: Building Blocks and Design Topologymentioning
confidence: 99%
See 3 more Smart Citations
“…1(c). All the parameters are optimized according to our previous work reported in [10]. The MZI consists of two 2 × 2 multimode interferometers (MMIs) connected by 4 µm wide Si waveguides with 100 µm long S-bend to prevent the thermal crosstalk induced by 200 µm long and 6 µm wide Titanium-tungsten (TiW) phase shifter placed between the two MMIs and 2 µm above one of the MZI balanced paths (Fig.…”
Section: Building Blocks and Design Topologymentioning
confidence: 99%
“…Our previous work investigated the 2 × 2 mode insensitive switch for the first three quasi-transverse electric modes, and it exhibits a good extinction ratio, bandwidth, reasonable insertion loss, and crosstalk [10]. It was observed that most of the insertion losses came from the mode MUX and deMUX.…”
Section: Building Blocks and Design Topologymentioning
confidence: 99%
See 2 more Smart Citations
“…More importantly, we found that this shallowly etched slot scheme had some scalability for the mode-order conversion, and more higher-order modes could be generated using such etched multimode waveguide structures. Based upon these unique features, the proposed scheme and related devices would well support the on-chip multimode applications [26,27], such as on-chip MDM systems.…”
Section: Introductionmentioning
confidence: 97%